Towards developing commercialized real-time PCR kits for the detection of avian pathogens. - Omar, Abdul Rahman; Ideris, Aini; Bejo, Mohd Hair; Syed Hassan, Syarifah; Yusoff, Khatijah; Arshad, Siti Suri (2005)
Various formats of polymerase chain reaction (PCR) detection methods such as conventional/nested agarose, colorimetric and in situ have been developed and tested against important avian viruses. However, most of these techniques failed to detect and differentiate vaccine and field strains. Even though PCR is a sensitive detection method, the importance of positive detection of an agent in terms of disease manifestation is poorly characterized. Recent studies using real-time PCR shows great promises in the detection and quantification of specific pathogens. Our group has been interested to develop and validate real-time PCR assay for important avian pathogens such as Newcastle disease virus (NDV), avian influenza virus (AIV), infectious bursa disease virus (IBDV), infectious bronchitis virus (IBV) and chicken anaemia virus (CAV). By using a novel real-time PCR technology we have developed an assay that is able to detect different strains of IBDV (Malaysian Patent PI 20044610). The optimized PCR technology was transformed into a prototype kit, IBDReal Check. The performance of the kit in comparison to other established IBD detection tests are currently being tested using both control experimental and clinical bursal samples. Work is underway on the development of patented PCR technologies for the detection of other important avian pathogens such as NDV and AIV.